Von Willebrand factor propeptide variants lead to impaired storage and ER retention in patient‐derived endothelial colony‐forming cells. (3rd May 2022) - Bowman, Mackenzie; Casey, Lara; Selvam, Soundarya N.; Lima, Patricia D. A.; Rawley, Orla; Hinds, Megan; Tuttle, Angie; Grabell, Julie; Iorio, Alfonso; Walker, Irwin; Lillicrap, David; James, Paula
Abstract: Background: von Willebrand factor (VWF) is synthesized by vascular endothelial cells and megakaryocytes. The VWF propeptide is critical for multimerization and acts as an intra‐molecular chaperone for mature VWF in sorting to its storage organelles, Weibel‐Palade bodies (WPBs). In the Canadian Type 3 VWD study, almost half of the identified variants were in the VWF propeptide and these were associated with an increased bleeding phenotype. Objective: To investigate VWF propeptide variants that cause quantitative von Willebrand disease (VWD) by utilizing patient‐derived endothelial colony‐forming cells (ECFCs). Patients/Methods: Endothelial colony‐forming cells were isolated from five Type 3 VWD patients from four families with the following variants: (1) homozygous p.Asp75_Gly178del (deletion of exons 4 and 5 deletion; Ex4‐5del), (2) homozygous p.Cys633Arg, (3) homozygous p.Arg273Trp, and (4) p.Pro293Glnfs*164 and p.Gln419* inherited in the compound heterozygous state. Additionally, ECFCs were isolated from six family members (two Type 1 VWD, four unaffected). Results: Endothelial colony‐forming cells from the Type 3 patient with the compound heterozygous genotype exhibited a true null VWF cellular phenotype, with negligible VWF detected. In contrast, the other three propeptide variants presented a similar expression pattern in homozygous ECFCs where VWF was synthesized but not packaged in WPBs, and variant VWF had an increased association with the endoplasmic reticulum (ER) marker, protein disulfide‐isomerase (PDI), indicating an ER‐retention phenotype. The biosynthetic phenotype was similar but to a lesser degree in heterozygous ECFCs expressing the non‐null variants. Conclusion: This study further elucidates the importance of the VWF propeptide in the VWD phenotype using patient‐derived cells.